The price of experience : writings on living with cancer - Marqusee, Mike (OR Books, 2014)
Diagnosed with multiple myeloma, a type of blood cancer, six years ago, Mike Marqusee was at first reluctant to write about such a private condition. But he came to realize that writing provided a precious continuity with his work before the disease. It also allowed him to address a variety of insidious platitudes that surround illness, often connected to the individualistic idea that the sufferer must be "brave." And so Marqusee began to write about his symptoms and feelings, the responses of friends to the news that he was ill, and the way these reflected broader attitudes. He described the political struggles occurring in the London hospital that continues to care for him, and the crisis in Britain's National Health Service (NHS). Big Pharma, whose drugs keep Marqusee alive but which are sold to the NHS at extortionate prices, fell under particularly astringent scrutiny. The observations about cancer in these pages are never trite or sentimental. Rather they are acute, impassioned, and political. And they convey important, shared truths, both personal and social, about an illness that will affect one in three people.